2023
DOI: 10.1021/acs.est.3c05246
|View full text |Cite
|
Sign up to set email alerts
|

Valorizing the Steel Industry Off-Gases: Proof of Concept and Plantwide Design of an Electrified and Catalyst-Free Reverse Water–Gas-Shift-Based Route to Methanol

Evangelos Delikonstantis,
Panagiotis Vettas,
Fabio Cameli
et al.

Abstract: Conversion of steel industry off-gases to value-added chemicals enabled by renewable electricity can significantly reduce the environmental burden of the steelmaking process. Herein, we demonstrate that CO2 reduction by H2, both contained in steel mill off-gases, to form syngas via the reverse water–gas-shift reaction is effectively performed by nanosecond pulsed discharges at atmospheric pressure. The experimental results suggest the following: (i) An optimum interelectrode distance exists, maximizing CO2 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…In the very first attempt toward electrification of the conventional CAMERE process, de la Fuente et al replaced the thermo-catalytic RWGS reactor with a microwave (MW) plasma-assisted one . The application of nonthermal MW plasma RWGS reactors demonstrated a trade-off between energy efficiency and CO 2 conversion, with the latter reaching 82% when the feedstock included only H 2 and CO 2 (H 2 /CO 2 molar ratio of 3). MW plasma noncatalytic reactors are scalable and feature high energy efficiency and lower cooling demand when the plasma is ignited at subatmospheric pressure (<0.1 bar) since a nonthermal plasma is favored. , Recently, Delikonstantis et al demonstrated that the RWGS reaction can also be enabled at atmospheric pressure by a nonthermal plasma, employing a nanosecond pulsed plasma …”
Section: Introductionmentioning
confidence: 99%
“…In the very first attempt toward electrification of the conventional CAMERE process, de la Fuente et al replaced the thermo-catalytic RWGS reactor with a microwave (MW) plasma-assisted one . The application of nonthermal MW plasma RWGS reactors demonstrated a trade-off between energy efficiency and CO 2 conversion, with the latter reaching 82% when the feedstock included only H 2 and CO 2 (H 2 /CO 2 molar ratio of 3). MW plasma noncatalytic reactors are scalable and feature high energy efficiency and lower cooling demand when the plasma is ignited at subatmospheric pressure (<0.1 bar) since a nonthermal plasma is favored. , Recently, Delikonstantis et al demonstrated that the RWGS reaction can also be enabled at atmospheric pressure by a nonthermal plasma, employing a nanosecond pulsed plasma …”
Section: Introductionmentioning
confidence: 99%